2017
DOI: 10.1093/mnras/stx2006
|View full text |Cite
|
Sign up to set email alerts
|

Rapid X-ray variability properties during the unusual very hard state in neutron-star low-mass X-ray binaries

Abstract: Here we study the rapid X-ray variability (using XMM-Newton observations) of three neutron-star low-mass X-ray binaries (1RXS J180408.9-342058, EXO 1745-248, and IGR J18245-2452) during their recently proposed very hard spectral state (Parikh et al. 2017). All our systems exhibit a strong to very strong noise component in their power density spectra (rms amplitudes ranging from 34% to 102%) with very low characteristic frequencies (as low as 0.01 Hz). These properties are more extreme than what is commonly obs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 57 publications
3
31
0
Order By: Relevance
“…They find N H = 0.24 × 10 22 cm −2 which is also consistent. This supports the notion that the emission in our XRT data is not due to the burst and likely an expression of the strong variability inferred by Wijnands et al (2017). We, therefore, refrain from further discussing this event.…”
Section: Burst From Igr J18245-2452supporting
confidence: 87%
“…They find N H = 0.24 × 10 22 cm −2 which is also consistent. This supports the notion that the emission in our XRT data is not due to the burst and likely an expression of the strong variability inferred by Wijnands et al (2017). We, therefore, refrain from further discussing this event.…”
Section: Burst From Igr J18245-2452supporting
confidence: 87%
“…Ten neutron stars have been monitored after accretion outbursts with the aim to study how their accretion-heated crusts cool in quiescence (see Wijnands et al 2017, for a review). The high temperatures observed within the first few hundred days of quiescence require an additional source of energy to heat the crust (e.g.…”
mentioning
confidence: 99%
“…This work reports on all three spectral states in a broad energy range (0.8-200.0 keV) and, in particular, the only data set that has high-quality broadband X-ray data available in the peculiar spectral/timing state, i.e., the so-called very hard state by Parikh et al (2017) and Wijnands et al (2017). Both the persistent and X-ray burst emission have been analyzed in this work.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism for producing such a hard spectrum remained unclear. Wijnands et al (2017) used two XMM-Newton observations to study the rapid variability properties of 1RXSJ180408.9−342058: one obtained early during the outburst in March 6 (see also Ludlam et al 2016) and one just before the transition to the soft state on April 1. These authors reported the source exhibited an unusually strong noise component, particularly during the first XMM-Newton observation.…”
Section: Introductionmentioning
confidence: 99%